Neurobiological mechanisms supporting experience-dependent resistance to social stress. (16th April 2015) - Cooper, M.A.; Clinard, C.T.; Morrison, K.E.
Highlights: Stress resilience is an active process that involves distinct neural circuits. Experience-dependent neural plasticity in key brain regions supports resilience. Dominant hamsters show resistance to the effects of social defeat. Neural plasticity in vmPFC circuits supports stress resistance in dominant hamsters. Abstract: Humans and other animals show a remarkable capacity for resilience following traumatic, stressful events. Resilience is thought to be an active process related to coping with stress, although the cellular and molecular mechanisms that support active coping and stress resistance remain poorly understood. In this review, we focus on the neurobiological mechanisms by which environmental and social experiences promote stress resistance. In male Syrian hamsters, exposure to a brief social defeat stressor leads to increased avoidance of novel opponents, which we call conditioned defeat. Also, hamsters that have achieved dominant social status show reduced conditioned defeat as well as cellular and molecular changes in the neural circuits controlling the conditioned defeat response. We propose that experience-dependent neural plasticity occurs in the prelimbic (PL) cortex, infralimbic (IL) cortex, and ventral medial amygdala (vMeA) during the maintenance of dominance relationships, and that adaptations in these neural circuits support stress resistance in dominant individuals. Overall, behavioral treatments that promote success in competitive interactions may represent valuable interventions for instilling resilience.